Mixed-function oxidases and esterases associated with cross-resistance between DDT and lambda-cyhalothrin in Anopheles darlingi Root 1926 populations from Colombia (2009)
ABSTRACT: In order to establish the insecticide susceptibility status for Anopheles darlingi in Colombia, and as part of the National Network on Insecticide Resistance Surveillance, five populations of insects from three Colombian states were evaluated. Standardised WHO and CDC bottle bioassays, in addition to microplate biochemical assays, were conducted. Populations with mortality rates below 80% in the bioassays were considered resistant. All field populations were susceptible to deltamethrin, permethrin, malathion and fenitrothion. Resistance to lambda-cyhalothrin and DDT was detected in the Amé-Beté population using both bioassay methods with mortality rates of 65-75%. Enzyme levels related to insecticide resistance, including mixed function oxidases (MFO), non-specific esterases (NSE), glutathione S-transferases and modified acetylcholinesterase were evaluated in all populations and compared with a susceptible natural strain. Only mosquitoes from Amé-Beté presented significantly increased levels of both MFO and NSE, consistent with the low mortalities found in this population. The continued use of lambdacyhalothrin for An. darlingi control in this locality has resulted in a natural resistance to this insecticide. In addition, DDT resistance is still present in this population, although this insecticide has not been used in Colombia since 1992. Increased metabolism through MFO and NSE may be involved in cross-resistance between lambdacyhalothrin and DDT, although kdr-type nerve insensitivity cannot be discarded as a possible hypothesis. Additional research, including development of a kdr specific assay for An. darlingi should be conducted in future studies. Our data demonstrates the urgent need to develop local insecticide resistance management and surveillance programs throughout Colombia.